ChemInform Abstract: Asymmetric Organocatalytic Quadruple Cascade Reaction of 2‐Hydroxychalcone with Cinnamaldehyde for the Construction of Tetrahydro‐6H‐benzo[c]chromene Containing Five Stereocenters. Issue 50 (16th December 2014) - Liu, Lingyan; Zhu, Yunna; Huang, Kaimeng; Wang, Bing; Chang, Weixing; Li, Jing
Abstract An oxa‐Michael—Michael—Michael‐aldol condensation cascade provides complex benzochromane derivatives starting from simple 2‐hydroxychalcones and cinnamaldehydes.